Prediction of Postoperative Range of Motion after Mobile-Bearing Medial Unicompartmental Knee Arthroplasty from the Preoperative Range of Motion and Other Preoperative Factors - Anjiki, Kensuke; Hiranaka, Takafumi; Tanaka, Toshikazu; Fujishiro, Takaaki; Okamoto, Koji; Hayashi, Shinya; Kuroda, Ryosuke; Matsumoto, Tomoyuki (The Journal of Knee Surgery, 2024)
Postoperative flexion after unicompartmental knee arthroplasty might be predicted from the preoperative range of motion and other preoperative factors, but this has not been sufficiently investigated. Between 2013 and 2017, 198 patients (198 knees) underwent unilateral knee arthroplasty with medial mobile-bearing unicompartmental knee arthroplasty. Range of motion was measured preoperatively and at the time of final follow-up. To investigate the accuracy of the prediction of preoperative to postoperative gain or loss of the flexion angle, we performed receiver operating characteristic analysis. Logistic regression analysis was used to evaluate other predictive factors. Change in flexion angle was significantly strongly and negatively correlated with the preoperative flexion angle (R = − 0.688; 95% confidence interval: −0.755 to −0.607; p < 0.001). Preoperative flexion angle was suggested to be a significant predictor of gain or loss of the flexion angle with the area under the curve of 0.781; the cutoff value calculated using the Youden index was 140 degrees. Logistic regression analysis showed that in addition to the preoperative flexion angle of the operated side, the postoperative flexion range was significantly affected by the patient's height and by the preoperative flexion angle of the contralateral knee. If the preoperative flexion angle in Oxford mobile-bearing medial unicompartmental knee arthroplasty is <140 degrees, the postoperative flexion angle may be improved; if it exceeds 140 degrees, the postoperative flexion angle may worsen. This predictive ability is further improved by consideration of the patient's height and the range of motion on the contralateral side.
Keywords: knee joint; UKA; flexion angle; ROC analysis; logistic regression analysis